The Unintended Consequences Of Tax Exemption Policy On Land And Building Tax - Hutapea, Elfrida; Gultom, Yohanna M. Lidya (Eduvest - Journal of Universal Studies, 2024)
This study aims to examine the unintended consequences of tax exemption policy on Land and Building Tax (PBB) for Sales Value of Tax Objects (NJOP) on properties under Rp 1 billion. Using Ordinary Least Square (OLS), this study analyzes data from PBB and BPHTB (Land and Building Rights Acquisition Fees) on the land and building’s certifications as well as the sales and property transactions, during the period of 2012 to 2019 in 267 sub-district areas within DKI Jakarta. This study learnt that the greater the number of the tax entities that received tax exemption in one sub-district, the greater the number of certifications as well as transactions (sales and purchases of property) under Rp 1 billion. This was consistently found within the sub-districts that were included in the non-flood-prone category, but not within the flood-prone sub-districts where the correlation was only significant for the certifications